Perlindungan Tenaga Kerja Migran Dari Kejahatan Lintas Negara Dalam Upaya Penegakan Hak Asasi Manusia - Auliaillah, Dhini; Ilmih, Andi Aina (Media Hukum Indonesia (MHI), 2024)
Every sovereign state has characteristics that identify it as an independent entity. Among them are the existence of residents or citizens, jurisdiction covering sea, land and air, as well as government structures regulated by their respective national laws. The constitution is the juridical, philosophical and sociological basis for organizing the lives and welfare of its citizens. Citizens of a country are not only subject to positive law or their own national law, but also to international law voluntarily, although it is not absolutely binding. Various conventions under the auspices of international organizations such as the UN have been agreed to comply with universal rules, such as conventions that protect workers or migrant workers who operate across jurisdictions between countries. In the context of protecting transnational migrant workers, it is important to understand legal arrangements from both national and international perspectives. In Indonesia, legal arrangements for migrant workers are regulated in various laws such as the Immigration Law, Employment Law, Smuggling Law, as well as various articles in the Criminal Code.